Answer:
x=9
Step-by-step explanation:
Step 1: Simplify both sides of the equation.
12=x+3
Step 2: Flip the equation.
x+3=12
Step 3: Subtract 3 from both sides.
x+3−3=12−3
Answer:
Step-by-step explanation:
304
<span>1.Describe how the graph of y = x2 can be transformed to the graph of the given equation.
y = (x+17)2
Shift the graph of y = x2 left 17 units.
2.Describe how the graph of y= x2 can be transformed to the graph of the given equation.
y = (x-4)2-8
Shift the graph of y = x2 right 4 units and then down 8 units.
.Describe how to transform the graph of f into the graph of g.
f(x) = x2 and g(x) = -(-x)2
Reflect the graph of f across the y-axis and then reflect across the x-axis.
Question 4 (Multiple Choice Worth 2 points)
Describe how the graph of y= x2 can be transformed to the graph of the given equation.
y = x2 + 8
Shift the graph of y = x2 up 8 units.
Question 5 (Essay Worth 2 points)
Describe the transformation of the graph of f into the graph of g as either a horizontal or vertical stretch.
f as a function of x is equal to the square root of x and g as a function of x is equal to 8 times the square root of x
f(x) = √x, g(x) = 8√x
vertical stretch factor 8
Plz mark as brainlest</span>
200 m to 4 hours
200/4
50m/1hour
Answer:
Tn=a + (n-1)d
a= first term = 14
n= This is the term you're looking for... In this case... That's the 73rd term
d=Common difference (since its an AP)
d= second term - first term -- Or 3rd term - 2nd term = 23-14
d=9
T = 14 + (73-1)9
T= 14 + (72)9
T= 14 + 648
T=662.